THE SOCIAL CONSTRUCTION OF EMOTIONS IN THE BHAGAVAD GĪTĀ - Johnson, Kathryn Ann (Journal of religious ethics, 2007)
Religious texts and historical narratives are instrumental in defining appropriate emotions and moral reasoning in a culture. In the Bhagavad Gıtā, the warrior Arjuna is faced with a twofold dilemma: are his emotions appropriate and should emotions influence his actions? The Gıtā is thought to be a redacted text with three primary layers: the original verses, the Sāmkhya/Yoga layer, and the devotional bhakti layer. Cross-cultural psychological theories of emotions are employed to analyze the layers of the Gıtā. It is argued that each of the three layers corresponds with one of three possible moral codes as proposed by R. A. Shweder and his colleagues (1997; 2000): the Ethic of Autonomy (promoting personal well-being and avoiding shame); the Ethic of Community (maintaining social order and emotional detachment); and the Ethic of Divinity (upholding cosmic order and endorsing emotional devotion). These three perspectives remain relevant for deciding emotionally laden moral dilemmas today.